Konsep Integrasi Pendidikan - Faishal (el Hakim Press, 2017)
Functions and objectives set by the government as stated in Law No. 20 of 2003 on National Education System, Article 3, that national education goal is to develop students' potentials to become a man of faith and fear of God Almighty, noble, healthy, knowledgeable, skilled, creative, independent, and become citizens of a democratic and responsiblewill be difficult to achieve during use patterns and approaches that separate educational institutions as long as there is a separation between schools, madrassah and boarding schools.Because of out put who graduated from educational institutions have different qualifications between one another.To prevent gaps at once to find common ground on these issues, there arose the idea to develop schools with integral system / integrated, an educational model that is designed to integrate from various sides and aspects of education, which includes a vision, mission, curriculum, educators, learning environment, and so forth.With the hope that the school forms able to build, establish, develop, and direct students to become whole human beings. People who have a positive character and personality, the man who is able to understand themselves and others, skilled human life, people are independent and responsible, and people who are willing and able to participate and cooperate with others.So that the separation of these institutions needs to be done by integrating the changes between the institutions. Empirically so that through this article tries to present the concept of integration of education in terms of the basic ideas, forms of integration and support components in the administration.